Three-Dimensional Multilayered Devices for Biomedical Applications - Costa, Rui R. (2015)
This chapter focuses on the use of layer-by-layer (LbL)-based strategies to conceive three-dimensional (3D) multilayered devices. It considers as 3D LbL device any multilayer coating (i) in which the template is removed after the construction, (ii) does not require retaining the template to perform its end, and (iii) is able to retain its integrity and function. This is followed by a discussion on the fabrication of structures with different geometries, such as freestanding membranes, spherical and anisotropic capsules, tubular and porous structures, and compartmentalized/hierarchical organization structures, as well as their potential applications in biomedical engineering. At present, it is clear that LbL-based devices may be fabricated with distinct structural properties, such as size, shape, mechanical properties, and compartmentalization, making them promising alternatives for biomedical applications that include wound healing, drug delivery, biosensors, tissue analogues, confined and hierarchical reactors, and cellular growth supports.